C and V : 80th exhibition by Artists of Chicago and Vicinity. - The Art Institute of Chicago (Chicago : The Art Institute of Chicago, 1984)
Adler, Iris ; Agne, Robert ; Allison, Jerry ; balsham, Leah ; Baum, Don ; Bohrod, Aaron ; Boone, Charles ; Bower, David ; Boyce, Christopher ; Bramson, Phyllis ; Buchman, Kaye Ann ; Bujnowski, Joel ; Coleman, Gene ; Collyer, Michael ; Conger, William ; Corefield, Elease ; etc.
C and V : 80th exhibition by Artists of Chicago and Vicinity, The Art Institute of Chicago, March 24 - May 6, 1984
boek